2017
DOI: 10.1177/1077546317732205
|View full text |Cite
|
Sign up to set email alerts
|

Transverse vibration analysis of composite thin annular plate by wave approach

Abstract: In this paper, free vibration and transmission properties of single and composite thin annular plate (TAP) structures are presented by wave approach. The propagation matrix, continuity matrix and reflection matrix are introduced to carry out the analysis. Using the wave approach, natural frequencies of single and composite TAP are calculated theoretically. The results obtained by this method agree well with those calculated by the classical Bessel and Hankel methods. Additionally, transfer matrix is introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Bahrami and Teimourian (2017) applied the wave approach to analyze the vibration, wave transmission and reflection in composite rectangular membranes. Liu et al (2018) deduced the propagation matrix and reflection matrix for predicting the free vibration for the transverse vibration of composite thin annular plate using wave approach. Furthermore, the transmission response of composite annular structures is also analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahrami and Teimourian (2017) applied the wave approach to analyze the vibration, wave transmission and reflection in composite rectangular membranes. Liu et al (2018) deduced the propagation matrix and reflection matrix for predicting the free vibration for the transverse vibration of composite thin annular plate using wave approach. Furthermore, the transmission response of composite annular structures is also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, wave approach has been applied to analyze the radial vibration (Liu et al 2016) and transverse vibration (Liu et al 2018) of annular plate. However, to the author's knowledge, few studies on torsional vibration can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results obtained by finite difference method were compared with those calculated by harmonic differential quadrature method, whose feasibility is verified by Bakhshi Khaniki and Hosseini-Hashemi [8]. Liu et al [9] construct the composite thin annular plate by wave approach. However, composite structures with multilayer are not studied.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, parameters are continuous for the connection. In recent years, many researchers describe the waves in the matrix forms [8][9][10][11][12][13][14][15][16][17].…”
Section: Propagation Matricesmentioning
confidence: 99%